STRATEGI PEMERINTAH DALAM PENERIMAAN ADIPURA DI KABUPATEN MAROS - Zulfikar Zulfikar; Djuliati Saleh; Andi Rosdianti Razak (Department of Public Administration, Muhammadiyah University of Makassar, 2015)
The purpose of this study was to find out government’s strategy in the reception Adipura’s award Maros regency. The type of research is qualitative method. 9 informants were selected according to its relevance to the study. The results showed that the government’s strategy Maros regency, when seen from a management functional strategy by way of Implementating and controlling, were optimal. Furthmore, the next strategy is done by local governmen namely revitalization garbage by 3R (reduce, reuse, amd recycle) and procurement of Green Open Space (GOS) has been highly optimized (already meets 30%). The supporting factors among other are dissemination to the public, special organization structure, the driving team, regular cleaning, waste banks, and RTH ( green space) in the district of Maros.Keywords : strategy, government, hygiene, environment Tujuan penelitian ini adalah untuk mengetahui strategi yang dilakukan Pemerintah Kabupaten Maros dalam penerimaan Adipura. Jenis penelitian yang digunakan adalah kualitatif. Informan sebanyak 9 orang yang dipilih sesuai dengan keterkaitannya dengan penelitian. Hasil penelitian menunjukkan strategi yang dilakukan Pemerintah Kabupaten Maros, jika dilihat dari strategi fungsional manajemen dengan cara implementating dan controlling, sudah optimal. Selanjutnya strategi pemerintah daerah dilakukan dengan cara revitalisasi sampah dengan 3R (reduce, reuse dan recycle) dan pengadaan Ruang Terbuka Hijau (RTH) sudah sangat optimal (sudah memenuhi 30%). Adapun faktor pendukung antara lain yaitu sosialisasi kepada masyarakat, struktur organisasi khusus, tim penggerak, pembersihan rutin, Bank Sampah, dan RTH di Kabupaten Maros.Kata kunci : strategi, pemerintah, kebersihan, lingkungan